Campylobacter jejuni and Campylobacter coli infection, determinants and antimicrobial resistance patterns among under-five children with diarrhea in Amhara National Regional State, Northwest Ethiopia - Worku, M.; Tessema, B.; Ferede, G.; Ochieng, Linnet; Leliso, S.A.; Mutua, Florence; Moodley, Arshnee; Grace, Delia; Gelaw, B. (2024)
Background: Children with under-five year age disproportionally affected with foodborne illness. Campylobacteriosis is the most common foodborne disease next to Norovirus infection. Macrolides are commonly prescribed as the first line of treatment for Campylobacter gastroenteritis, with fluoroquinolone and tetracycline as secondary options. However, resistance to these alternatives has been reported in various regions worldwide.